2011
DOI: 10.1088/1742-6596/333/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and velocity statistics of inertial particles in turbulent flows

Abstract: Abstract. Spatial and velocity statistics of heavy point-like particles in incompressible, homogeneous, and isotropic three-dimensional turbulence is studied by means of direct numerical simulations at two values of the Taylor-scale Reynolds number Re λ ∼ 200 and Re λ ∼ 400, corresponding to resolutions of 512 3 and 2048 3 grid points, respectively. Particles Stokes number values range from St ≈ 0.2 to 70. Stationary small-scale particle distribution is shown to display a singular -multifractal-measure, charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
4
30
0
Order By: Relevance
“…The efficiency in the Hall table is quite small, and below 0.5 for droplets with a radius of about 30 μm, which are computed for the laminar flows. However, since other studies have reported that the turbulence enhances droplet collisions, it is expected that the collision efficiency of droplets in turbulent flows would be between those for the Hall table and unity [5,6,8,9,11,14,18,19,[57][58][59].…”
Section: Collision-coalescencementioning
confidence: 96%
See 2 more Smart Citations
“…The efficiency in the Hall table is quite small, and below 0.5 for droplets with a radius of about 30 μm, which are computed for the laminar flows. However, since other studies have reported that the turbulence enhances droplet collisions, it is expected that the collision efficiency of droplets in turbulent flows would be between those for the Hall table and unity [5,6,8,9,11,14,18,19,[57][58][59].…”
Section: Collision-coalescencementioning
confidence: 96%
“…The central issue in such research has been the growth of the droplet spectrum (size distribution), especially the broadening of the distribution over time. Turbulence fluctuations affect the spatial distribution of cloud condensation nuclei (CCN) and cloud droplets, thereby enhancing droplet clustering via intermittency [5,6,8,11,15,18,19,57,58,76], and supersaturation fluctuations broaden the size distribution of cloud droplets depending on the number density of the aerosols [10,55].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent investigations (e.g. [9][10][11]) have shown that for finite St, S p 2 may deviate significantly from the smooth scaling behavior of S f 2 in the dissipation range (i.e. η ≪ r ), and this has been explained in terms of the formation of 'caustics' (also referred to as the 'sling effect' [12,13] and 'random uncorrelated motion' [14,15], although it should be noted that random uncorrelated motion is really a statistical manifestation of caustics, which are instantaneous events).…”
Section: Introductionmentioning
confidence: 99%
“…The collision process of particles in turbulent flow, and its statistical properties, have been studied extensively since Saffman and Turner [18]. Many studies have analytically and numerically examined particle density [19,20], collision frequency [21][22][23][24], and various influences on collision efficiency such as sedimentation [25][26][27], the clustering and spatial distribution of the inertial particles [28][29][30][31][32][33][34][35][36], and the hydrodynamic interaction [37][38][39]. It was found that the collision of cloud droplets with a similar size depends on the Stokes number t t = St p K , where t p and t K are the characteristic time of the droplet and the Kolmogorov time of turbulent flow, respectively, and becomes frequent for ( ) = St O 1 , at which the droplet radius is about 30 μm.…”
Section: Introductionmentioning
confidence: 99%